Factors affecting the effectiveness of financial management information system - Hartikayanti, Heni Nurani; Bramanti, Frita Lussie; Gunardi, Ardi (International Journal of Engineering and Technology, 2018)
This study aims to analyze the factors that influence the effectiveness of management information system in the financial institution. Data were distributed to the managers in financial areas ranging from middle to top management level in Cimahi. The respondents in this study are 49 people. This study uses a quantitative and descriptive approach. The method used is an associative method. Data analysis uses regression analysis model. The unit of analysis in this study is the financial manager in the village and sub-district of Cimahi. Financial managers at the top level and middle level interact directly in the utilization of information technology. The data testing is done through validity test with Spearman Rank correlation coefficient and reliability tests with Cronbach Alpha coefficient. As for descriptive data analysis, multiple regression analysis was used. The results showed that the sophistication of the technology, manager’s knowledge, and participation affect the effectiveness of implementation of financial management information system. The problem that needs to be corrected is the technology that is still inadequate to produce accurate and relevant information.